Impact of kombucha, coffee, and turmeric beverages on the color stability of a single-shade versus a multi-shade resin-based composite - Yeslam,Hanin E.; Bakhsh,Abdulaziz F. (PeerJ, 2025)
Currently, patients place great significance on both the appearance and health benefits of dental treatments. Single-shade resin-based composites (RBC) are commonly used in clinical practice, but various popular caffeinated and healthy drinks can lead to staining. This study aimed to compare the resistance of a newly introduced single-shade RBC with an advanced polymerization system (APS) to turmeric, kombucha, and coffee staining as compared to that of a conventional multi-shade RBC. Sixty specimens (8 × 5 × 2 mm) were created using two types of RBCs: a single-shade (Vittra APS Unique, FGM Dental Group, Joinville, SC, Brazil) and a conventional universal RBC (Tetric N-Ceram, Ivoclar Vivadent, Germany). The samples were randomly divided into two main groups (N = 30) based on the RBC used. Each group was further divided into three subgroups (n = 10) based on the storage media, including turmeric, kombucha, and coffee (positive control). Color readings were recorded after 0, 6, and 12 days of immersion. The mean color change (ΔE (both ΔE*ab and ΔE00)) values were statistically analyzed using repeated measure mixed design ANOVA and Bonferroni multiple comparisons (p < 0.05). The results of the study indicated that time had a statistically significant effect on ΔE (p < 0.001). The three-way interaction (time*material*solution) was also found to be statistically significant (p = 0.005). Turmeric caused a significantly higher ΔE compared to both coffee and kombucha (p < 0.001). Tetric N-Ceram exhibited a significantly lower ΔE than Vittra APS Unique (p = 0.004). In conclusion, with consideration of the limitations of the study, it can be stated that single-shade RBCs with APS are less color-stable than universal RBCs. The study also indicates that both kombucha and coffee can affect the color stability of RBCs, whereas turmeric has the most detrimental effect on the color of dental composites.
Keywords: Color change; Composite resin; Single-shade composite; Esthetics; Turmeric; Restorative dentistry; Probiotic drinks; Esthetics; Staining; Nanofilled composite